THE IMPLEMENTATION PROSPECTS OF A TYPICAL CROSS-CUTTING PROGRAM ON THE HIV PROBLEM AT MEDICAL BIOLOGY DEPARTMENT - Довганич, Н.В. (World of Medicine and Biology, 2015)
Acquired immune deficiency syndrome (AIDS) is an extremely dangerous infectious disease which is caused by the human immunodeficiency virus (HIV). Wide spread of the disease throughout the world and Ukraine threatens personal, social and national security, causing severe socio-economic and demographic consequences. As a result, there is a necessity to adopt appropriate measures to protect the rights and legitimate interests of citizens and the society. Ukraine occupies one of the leading places as to the rate of HIV spreading in the Eastern Europe. The V National Programme on HIV prevention, care and treatment of HIV and AIDS is carried out in Ukraine. A new State Government Strategy is being developed in order to coordinate the efforts aimed at preventing the spread of HIV. The health care system is already experiencing the negative impact of spreading HIV infection. The population now has a growing demand for health care. HIV-AIDS will exacerbate the already unfavorable demographic situation in Ukraine. Therefore, HIV-infection is a major health and social problem. It is a primary necessity to ensure implementation of the state policy in the field of HIV prevention in order to address the problems which are associated with: prevention of HIV transmission from mother to child; diagnosis and treatment of HIV-infected and their psychosocial support by means of joint efforts of the government, public, medical science and medical practice. It is necessary to train highly qualified health care personnel for solving of this problem. Tackling this problem will help facilitate the implementation of typical academic programme, approved by order № 313 on 08.05.2009. “On the Optimization of Specialist Training in HIV Prevention and Its Transmission from Mother to Child”. With this mind, the aim of this work is to introduce continuous academic programme into the educational process to improve the quality of modern physicians regarding health and social issues of HIV. There have been developed and updated guidelines, teaching materials, which provide efficient implementation of recommended topics on certain lectures, tutorials, elective courses in the educational process. After completion of the course, a doctor or nursing personnel will have sufficient knowledge and qualification to diagnose, keep clinical records and prevent HIV as well as participate in prevention programs for different age groups, especially for teenagers and youth.